PENGARUH MEDIA KONKRET DALAM PEMBELAJARAN MATEMATIKA MATERI PECAHANAN KELAS II UPT SDN 49 GRESIK - Harisatuz Zahro; Slamet Asari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the influence of concrete media in teaching mathematics for class II fractions at UPT SDN 49 Gresik. The subjects in this study were 54 students consisting of 27 students in the experimental group and 27 students in the control group. In this research, a quantitative research approach was used with a quasi-experimental research design with a non-equivalent control group design method using two groups, namely the experimental group and the control group. The data collection techniques used were observation and documentation using data analysis techniques, namely the Mann-Whitney U test. The results of data analysis were obtained from the Mann-Whitney U-Test test calculations using IBM SPSS Statistics 26, and obtained the known Asymp.Sig value. . (2 tailed) which is ,000. On the basis of decision making if Asymp.Sig. < 0.05, then there is a significant difference between the experimental group and the control group, where the experimental group's value is higher than the control group's value, so Ha is accepted and Ho is rejected. The results of the research can be concluded that concrete media has a significant influence on the ability to understand fractions in class II elementary school students. This is reinforced by the results of descriptive statistics in the experimental group which shows an increase in the ability to understand mathematics learning on the topic of fractions by 40, this result is very different from the control group, namely 18,7. So concrete media is very suitable for developing the ability to understand fractions in students. Apart from introducing fractions to students, the use of this media can also add variety to the learning process in class to increase children's interest and enthusiasm for learning.